HebQTLs reveal intra-subgenome regulation inducing unbalanced expression and function among bread wheat homoeologs - Xiaoming Wang; Yuxiu Liu; Peng Zhao; Wenyang Hou; Mingzhu Cheng; Xue Shi; James Simmonds; Philippa Borrill; Xiaojie Wang; Wanquan Ji; Shengbao Xu (Genome Biology)
Abstract Background Polyploidy contains multiple gene copies, known as homoeologs. Differential expression of homoeologs confers expression plasticity and facilitates the adaptation and domestication of major polyploid crops. However, how this homoeolog expression bias is produced and genetically regulated remains elusive. Results Here we uncover substantial variation in homoeolog expression bias among the root transcriptomes of a natural population of 406 bread wheat (Triticum aestivum ssp. aestivum) accessions collected worldwide. We develop a new model allowing us to identify 14,727 quantitative trait loci regulating the variation in homoeolog expression bias (hebQTLs), indicating that homoeolog expression bias is genetically regulated and can be predicted using genotyping data. The hebQTLs mostly regulate the expression of homoeologs in the same subgenome and downregulate expression to produce homoeolog expression bias, suggesting that intra-subgenomic rather than inter-subgenomic interactions induce homoeolog expression bias. Furthermore, we determine that hebQTL-regulated homoeologs exhibit higher genetic diversity and weaker biological functions than their counterparts. Notably, the downregulation of 38.4% of hebQTL-regulated homoeologs is compensated for by the upregulation of other homoeologs within the triad. Conclusions Our findings reveal how homoeolog expression is coordinated at the genetic level and provide an avenue for leveraging homoeolog expression bias to improve polyploid crops.